REAL SCIENTISTS DON'T WEAR TIES when science meets culture. - Perkowitz, Sidney ([S.l.] : PAN STANFORD PUBLISHING, 2019)
Real Scientists Don't Wear Ties links science to general and popular culture and everyday life in an easy-to-understand style. When a gifted writer of science selects his best pieces published in the world's most reputable periodicals such as Nature, Discover, and MIT Technology Review, we get an eminently readable collection of his varied work in book form. That it covers all-time relevant topics like quantum physics, gravitational waves, genetic engineering, space exploration, and artificial intelligence is an added delight. Prof. Perkowitz also discusses how science can be found in medical practice, cooking, soccer, and art, and also science and science fiction in the media. On the lighter side, he reports on his efforts to teach a computer to understand poetry, explains why scientists resist dressing up, and shows that unlike many people, scientists actually enjoy math.
OCLC-licensed vendor bibliographic record.
Keywords: Science in popular culture; MATHEMATICS / General; MATHEMATICS / Recreations & Games; SCIENCE / Chemistry / General